Association between daytime nap duration and risks of frailty: Findings from the China Health and Retirement Longitudinal Study - Zhang, Yan; Zhou, Lixing; Ge, Meiling; Lin, Xiufang; Dong, Birong (Frontiers in Public Health, 2023)
Introduction Night sleep duration and total sleep duration are associated with frailty. However, the association between daytime nap duration and the risks of frailty has not been explored thoroughly. Methods This study used data from the China Health and Retirement Longitudinal Study (CHARLS). Participants aged 60 years and older at baseline were included in this study. Individuals with daytime nap duration were categorized into four groups: no napping, short napping (< 30 min), moderate napping (30–89 min), and extended napping (≥90 min). Frailty was assessed using a modified Physical Frailty Phenotype (PFP) scale. Non-frail participants at baseline were followed up for 4 years. The association between nap duration and risks of frailty at baseline and incident frailty was evaluated by logistic regression and discrete-time Cox regression analyses, respectively. Results In total, 5,126 participants were included in this study. For individuals with night sleep duration of ≥9 h, short nappers showed higher odds [odds ratio (OR) = 4.08, 95% confidence interval (CI): 1.30–12.78] for frailty compared with non-habitual nappers at baseline, while moderate nappers were less likely to be frail (OR = 0.18, 95% CI: 0.04–0.73). In the follow-up study, short nappers showed higher risks for frailty compared with participants of the no napping group with night sleep duration of < 6 h [hazard ratio (HR) = 1.91, 95% CI: 1.07–3.43] or 6–9 h (HR = 1.97, 95% CI: 1.18–3.30). Compared with short nappers, older adults with extended napping (HR = 0.41, 95% CI: 0.22–0.77) showed lower risks for frailty in those with night sleep duration of 6–9 h. For individuals with night sleep duration of ≥9 h, moderate napping (HR = 0.20, 95% CI: 0.05–0.77) decreased the risks for frailty compared with short napping. Conclusion Among older adults with night sleep duration of < 9 h, short nappers posed higher risks for frailty compared with non-habitual nappers. Extended naps for those with a night sleep duration of 6–9 h or moderate naps for those with night sleep duration of ≥9 h could lower the risk of frailty compared with short naps. Future studies on the timing, purpose, frequency, and quality of daytime napping and objectively measured nap duration are needed to explore the association between daytime napping and risks of frailty.